Kajian Teknis Alat Gali-Muat dan Alat Angkut Pada Pencapaian Pengupasan Overburden 1.120.000 BCM di Pit Taman Tambang Air Laya Bulan September 2016 PT Bukit Asam (Persero) Tbk - Irwan Edel Frudis; Mardiah Mardiah; Janiar Pitulima (Jurusan Teknik Pertambangan Universitas Bangka Belitung, 2018)
In the layer of overburden stripping activities in Pit Taman attainment production amounted about 82% of the production target set in the amount of 925,187.2 BCM of production target of 1,120,000 BCM. This is due to the high resistance factor affecting work efficiency so that production is produced by means of unloading and transportation have not been able to achieve the production target. The data obtained in the field in the form of a data cycle time tools obtained from the calculation of the time distribution of each trencher-fit to perform the excavation, swing content, swing empty and loading and conveyance maneuvering, loading, road to disposal, dumping and back to front as well as the calculation of effective working hours will do the calculation of the amount of productivity. After calculating the theoretically obtained by 1,656,454.08 BCM of overburden production for excavator-unloading and BCM 1,405,890.9 for conveyance. To get productivity achieve production targets then do the optimization tools work plan is to optimize. Optimizing plan working hours adjustment tools and repair equipment capacity are obtained overburden production amounted to 1,914,890.2 BCM. As for after the technical review of the excavator-unloading and conveyance in stripping overburden at Pit Taman in September 2016 on the calculation of production trencher-load transports that have been implemented should only use 3 units of excavator-unloading is 3 units of PC Komatsu 2000 for with the use of 3 units with improvements and performance optimization tools as well as the factors that influence has reached its production target of 1,670,167.71 BCM and for the use of conveyances using Komatsu HD 785 20 units with a production target of 1,615,712.8 BCM.